A Comparative Analysis of Gene Expression Profile in Liver and Esophageal Cancer using Expressed Sequence Tags - Mahboobeh Ramezani; Fatemeh Shamsabadi; Morteza Oladnabi (Golestan University Of Medical Sciences, 2019)
Background and objectives: Liver and esophageal cancers are common among the Iranian population. This study aims to explore the common up-regulated genes in liver and esophageal cancer tissues using expressed sequence tags (ESTs) and to identify the role of key genes in cancer development. Methods: EST profiles of protein-coding genes in normal and cancerous hepatic and esophageal tissues were extracted from the UniGene database. Genes with > 1500 transcripts per million were selected as highly expressed. The cancer to normal ratio of  up-regulated genes was calculated. The shared overexpressed genes between liver and esophageal cancer tissues were determined. Finally, functional classification and pathway analysis were performed on the genes using the STRING and Enrichr databases. Results: Of 17,242 genes, 53 and 26 genes were overexpressed in the liver and esophageal cancer tissues, respectively. Nine up-regulated genes (APLP2, EEF1G, ENO1, HSP90AA1, HSP90AB1, HSPA8, KRT18, RPL4 and UBC) were shared between the two cancer tissues, which were involved in cell cycle progression through G2/M checkpoint, G1/S transition and DNA replication. They were also involved in the vascular endothelial growth factor, hypoxia-inducible factor 1 and estrogen signal pathways as well as the Toll-like receptor cascade. Conclusion: Based on the results, the identically up-regulated genes and underlying molecular mechanisms implicated in both cancers could be valuable targets for diagnosis and treatment of cancer.